Positive criminology: reflections on care, belonging and security - Oude Breuil, Brenda; Schuilenburg, Marc; Steden, Ronald van (eleven international publishing, 2014)
"Safety and security are often seen in light of crime, disorder and fear. This fuels a political and social climate obsessed with a negative logic of 'fighting' criminals, 'controlling' populations, and 'excluding' unwanted others. Other, more positive or constitutive, discourses and practices about safety and security have fallen out of fashion. But, what alternatives to contemporary processes of securitization and criminalization can be imagined when starting from a positive critique of security? Which theoretical and empirical resources support and inspired more positive notions of security? This multidisciplinary volume brings together a team of renowned scholars to stress that security also includes notions of care, trust and belonging. By taking the concept of security beyond traditional criminal law, the scholars in this volume bring cutting-edge theoretical and empirical analyses on the importance of human connectedness, community building and feelings of solidarity as a way to resist hegemonic and negative meanings of security. This volume will appeal to researchers in the field of criminology, political science, sociology, philosophy and security studies"--Back cover